The devil in the deemed: Novel takes on Sections 198B and D - Govindjee, Avinash; Grogan, John (Obiter, 2020)
Section 198 of the Labour Relations Act is designed to protect vulnerable employees of labour brokers and those on fixed-term contracts. Some recent judgments may make obtaining that protection more complicated.